Peningkatan Nilai Tambah Produk Ekomomi Kreatif Masyarakat Melalui Pembuatan Olahan Dendeng Kerbau di Desa Tounwawan - Micael Ririhena; Braian Moriolkosu; Maria F. Uniwaly; Lydia Saraswati; Stenly Walalayo; Garance Usmany; Galfen Salow; Oktavia Borolla; Janni G. Kalabory; Maria N. Rahandekut; Helga Nahakleki; Ruth Lewier; Martafina Kosaplawan (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
Real Work Lecture (KKN) is a compulsory course for undergraduate students in the Study Program Outside the Main Campus (PSDKU) of Pattimura University. Through the KKN program, students are expected to be able to make a new innovation that can improve the community's economy. Based on observations in Tounwawan Village, it is known that Tounwawan Village is one of the villages in Moa District which has hilly areas, has extensive forests and fields. The majority of farmers in this village make buffalo as one of their income. So that the processing of buffalo meat into sweet jerky is one of the priority programs that can provide new innovations for the people of Tounwawan Village. This program aims to improve the economy of the community. The program will be held on July 15, 2023, on Saturday. Furthermore, the processing was attended by Tounwawan villagers together with the Management of Village-Owned Enterprises (BUMDes). Through this program, the community can improve the economy through innovation in processing buffalo meat into sweet jerky.